Specıfıcs Of Teachıng To Independent Thınkıng At Lıterature Lessons - Kunduzkhon Кhusanbayeva, Maksuda Saribaeva, Gulnoza Taylakova, Muxtor Yuldashev (International Journal of Advanced Science and Technology, 2020)
This article presents examples of fiction that teach students to think independently in the process of school literary education, the importance of independent thought in the process of shaping and implementing it. The article provides practical advice on differentiating the ghosts of AlisherNavoi and Nodira by following the example of Abdullah Kadiri’s novel The Past Days. This process is based on the views of a number of Uzbek and Russian scientists – pedagogues and psychologists. Based on these, certain conclusions were drawn.